(untitled) (Research, Society and Development, 2021)
Objective: To investigate the opinion of family farmers about the supply of organic food to the National School Feeding Program (PNAE) in the state of Paraná, Brazil. Method: The convenience sample consisted of 44 family farmers from nine cooperatives and associations located in eight different mesoregions of the state of Paraná that supplied organic food to the PNAE. An online survey was conducted to evaluate the farmers’ opinion on possible changes in the cooperatives’ revenue and organization; diversification and production increase; difficulties in commercialization; increase in income, and improvement in food consumption after supplying to the PNAE. Results: According to the farmers’ opinion, there was better organization (100%) and an increase in the cooperatives’ revenue and production (86.36%), after supplying to the PNAE. 75% of the farmers diversified their crops and 52.3% reported an increase of up to 25% in their family income. In addition, it was reported a better acceptance of the school feeding, diversification in the family’s diet, improved self-esteem, closeness between producers and consumers, and the return of family members to the rural property. Conclusion: In the opinion of family farmers, PNAE has been fulfilling its role as a promoter of Food and Nutritional Security in the development of healthy habits, besides contributing to the increase in family income and promoting local sustainable development, following the World Health Organization’s agenda.